2016
DOI: 10.1016/j.pharep.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoacridinone antitumor agent C-1311 as a selective mechanism-based inactivator of human cytochrome P450 1A2 and 3A4 isoenzymes

Abstract: Our results indicated that C-1311 is a potent mechanism-based inactivator of CYP1A2 and CYP3A4. This finding provided new insights into the mechanism of C-1311 antitumor action, particularly in relation to potential pharmacokinetic drug-drug interactions between C-1311 and/or its derivatives and the substrates of CYP isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The inhibition of topoisomerase II by C-1311 leads to the formation of cleavable DNA-topoisomerase II complexes and subsequent DNA strand breaks [ 2 ]. However, more recent studies have described additional roles for C-1311; the inhibition of tumor angiogenesis through the targeting of the HIF-1α/VEGF pathway [ 3 ], inactivation of the human cytochrome P450 1A2 and 3A4 isoenzymes [ 4 ], and inhibition of receptor kinases, most notably the FMS-like tyrosine kinase FLT3 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of topoisomerase II by C-1311 leads to the formation of cleavable DNA-topoisomerase II complexes and subsequent DNA strand breaks [ 2 ]. However, more recent studies have described additional roles for C-1311; the inhibition of tumor angiogenesis through the targeting of the HIF-1α/VEGF pathway [ 3 ], inactivation of the human cytochrome P450 1A2 and 3A4 isoenzymes [ 4 ], and inhibition of receptor kinases, most notably the FMS-like tyrosine kinase FLT3 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the metabolic profiles of C-1305 and C-1311 were not changed in MCF-7 and HCT116 cells after their overexpression with P4503A4 isoenzyme [47]. Thus, P4503A4 does not take part in the metabolism of studied acridinone derivatives, as we previously showed with recombinant isoenzymes in a non-cellular system [26,27] and in HepG2 cells [29,31]. EV.…”
Section: Metabolic Transformation Of C-1305 and C-1311 In Mcf-7 And Hmentioning
confidence: 59%
“…During long-term treatment of HCT116-CYP3A4 cells with C-1305 and C-1311, the activity of P4503A4 also gradually increased up to 96 h of incubation, then started to go down after 120 h. Concluding, we show that C-1305 and C-1311 are strong P4503A4 inducers. However, our previous studies in non-cellular systems revealed that C-1305 and C-1311 incubated with recombinant P4503A4 as its selective mechanism-based inactivator [25,26] but later in HepG2 cells showed that in living cells C-1305 increased activity of P4503A4 [50]. It suggests that the activation of P4503A4 catalytic properties does not result from direct interaction between the compounds and the P450 enzyme but through a cellular regulatory pathway and this activation is stronger than any direct drug inhibition features.…”
Section: Modulation Of P4503a4 and Ugt1a10 Activity By C-1305 And C-1311mentioning
confidence: 95%
See 1 more Smart Citation